2010
DOI: 10.1002/jbt.20308
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of liver samples from puffer fish Takifugu rubripes exposed to excessive fluoride: An insight into molecular response to fluorosis

Abstract: Comparative proteomics was performed to identify proteins in the liver of Takifugu rubripes in response to excessive fluoride exposure. Sixteen fish were randomly divided into a control group and an experimental group. The control group was raised in soft water alone (F(-) = 0.4 mg/L), and the experimental group was raised in the same water with sodium fluoride at a high concentration of 35 mg/L. After 3 days, proteins were extracted from the fish livers and then subjected to two-dimensional polyacrylamide gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Thus, gene expression profiling of the sperm cells from fluorideexposed mice has shown that 34 studied genes were upregulated and 63 genes were downregulated, most of which are involved in the signal transduction, amino acid phosphorylation, oxidative stress, cell cycle, electron transfer, glycolysis, chemotaxis, spermatogenesis, and apoptosis [105]. Comparative proteomic analysis of the kidney, liver, and cardiac muscle samples from puffer fish Takifugu rubripes exposed to excessive fluoride has revealed that among a few tens of proteins, found to be either upregulated or downregulated, five or more proteins seem to be involved in apoptosis and other functions associated with fluorosis [141][142][143]. Those are disulfide isomerase ER-60 playing a key role in the degradation of misfolded proteins and refolding of denatured proteins in ER, SMC3, and SMC4 proteins taking part in DNA recombination and repair, as well as chromosome segregation, 4NSc-Tudor domain protein (nuclear factor kappa B2 NF-kB2) which proapoptotic function is stabilization of p53, cyclin D1, a nuclear protein repressed by p53 and required for cell cycle progression, MAPK10 (c-Jun N-terminal kinase 3 JNK3), thought to phosphorylate p53 and playing an important role in nuclear signal transduction associated with apoptosis [144][145][146][147].…”
Section: Gene Expressionmentioning
confidence: 99%
“…Thus, gene expression profiling of the sperm cells from fluorideexposed mice has shown that 34 studied genes were upregulated and 63 genes were downregulated, most of which are involved in the signal transduction, amino acid phosphorylation, oxidative stress, cell cycle, electron transfer, glycolysis, chemotaxis, spermatogenesis, and apoptosis [105]. Comparative proteomic analysis of the kidney, liver, and cardiac muscle samples from puffer fish Takifugu rubripes exposed to excessive fluoride has revealed that among a few tens of proteins, found to be either upregulated or downregulated, five or more proteins seem to be involved in apoptosis and other functions associated with fluorosis [141][142][143]. Those are disulfide isomerase ER-60 playing a key role in the degradation of misfolded proteins and refolding of denatured proteins in ER, SMC3, and SMC4 proteins taking part in DNA recombination and repair, as well as chromosome segregation, 4NSc-Tudor domain protein (nuclear factor kappa B2 NF-kB2) which proapoptotic function is stabilization of p53, cyclin D1, a nuclear protein repressed by p53 and required for cell cycle progression, MAPK10 (c-Jun N-terminal kinase 3 JNK3), thought to phosphorylate p53 and playing an important role in nuclear signal transduction associated with apoptosis [144][145][146][147].…”
Section: Gene Expressionmentioning
confidence: 99%
“…F ion (mg/kg), protein (Pr) and calcium (Ca) level (%), and energy density (ED, MJ/kg) in the diet of the rabbits. differentially (Lu et al, 2010). In rat liver, enzymes of the antioxidative system, such as superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH), were significantly inhibited after NaF exposure (Blaszczyk et al, 2011).…”
Section: Introductionmentioning
confidence: 99%